2014
DOI: 10.3386/w19987
|View full text |Cite
|
Sign up to set email alerts
|

The Causal Effects of Competition on Innovation: Experimental Evidence

Abstract: In this paper, we design two laboratory experiments to analyze the causal effects of competition on step-by-step innovation. Innovations result from costly R&D investments and move technology up one step. Competition is inversely measured by the ex post rents for firms that operate at the same technological level, i.e. for neck and neck firms. First, we find that increased competition leads to a significant increase in R&D investments by neck and neck firms. Second, increased competition decreases R&D investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…Spending on R&D fosters employee creative activities, which enable firms to generate new products and processes that effectively satisfy dynamic needs of customers (Pike et al, ; Pateli and Lioukas, ). Given the importance of employee creativity in transferring R&D spending into innovative outcomes (Aghion et al, ), scholars have examined a variety of antecedents of employee creativity in R&D context (e.g., Tang, ; Yun and Lee, , Zhu et al, ), among which the role of leadership has attracted particular attention given the preeminent effect of leaders in influencing employee behavior (Elkins and Keller, ). In line of the inquiry, several studies have suggested that Leader‐Member exchange (LMX), which denotes the quality of exchange relationship between the dyad, facilitates employee creativity (e.g., Khazanchi and Masterson, ; Hemlin and Olsson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Spending on R&D fosters employee creative activities, which enable firms to generate new products and processes that effectively satisfy dynamic needs of customers (Pike et al, ; Pateli and Lioukas, ). Given the importance of employee creativity in transferring R&D spending into innovative outcomes (Aghion et al, ), scholars have examined a variety of antecedents of employee creativity in R&D context (e.g., Tang, ; Yun and Lee, , Zhu et al, ), among which the role of leadership has attracted particular attention given the preeminent effect of leaders in influencing employee behavior (Elkins and Keller, ). In line of the inquiry, several studies have suggested that Leader‐Member exchange (LMX), which denotes the quality of exchange relationship between the dyad, facilitates employee creativity (e.g., Khazanchi and Masterson, ; Hemlin and Olsson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such a self-reinforcing effect of market dominance is strongly supported by the experimental results. A recent study by Aghion et al (2014), implements the step-by-step model by Aghion et al (2001) in the lab, and finds support for the prediction that the effect of competition on innovation depends on the degree of asymmetry between firms.…”
Section: Research and Developmentmentioning
confidence: 83%
“…This suggests that the potential of simultaneity bias, while it cannot be ruled out, might be less concerning. Second, the literature has well acknowledged that competition in non-experimental studies is likely to be endogenous for the parameters of interest (Blundell et al 1999;Aghion et al 2018). Busso and Galiani (2019) provided the first randomised controlled field experiment designed to assess the impact of increasing competition on prices of various goods in the Dominican Republic.…”
Section: Tablementioning
confidence: 99%